Cognitive Achievement Production in Madagascar : A Value-Added Model Approach - Aubery, Frederic (Taylor and Francis, 2022)
In this paper, we measure the contribution of an additional year of schooling on skills acquisition for a cohort of young adults in Madagascar. We estimate a value-added model of learning achievement that includes test scores measured at adolescence, thereby reducing the potential for omitted variable bias. We demonstrate that schooling increases cognitive skills among young adults. The value-added of a year of schooling during adolescence is 0.15 to 0.26 standard deviation. Our results show the skills gap widens in adolescence, as students with higher cognitive skills complete more grades, accumulating more skills in their transition to adulthood.